CLASH: z ~ 6 young galaxy candidate quintuply lensed by the frontier field cluster RXC J2248.7-4431 - Monna, Anna; Bartelmann, Matthias (Arxiv, 2013)
We present a quintuply lensed z ~ 6 candidate discovered in the field of the galaxy cluster RXC J2248.7-4431 (z ~ 0.348) targeted within the Cluster Lensing and Supernova survey with Hubble (CLASH) and selected in the deep HST Frontier Fields survey. Thanks to the CLASH 16-band HST imaging, we identify the quintuply lensed z ~ 6 candidate as an optical dropout in the inner region of the cluster, the brightest image having magAB=24.81+-0.02 in the f105w filter. We perform a detailed photometric analysis to verify its high-z and lensed nature. We get as photometric redshift z_phot ~ 5.9, and given the extended nature and NIR colours of the lensed images, we rule out low-z early type and galactic star contaminants. We perform a strong lensing analysis of the cluster, using 13 families of multiple lensed images identified in the HST images. Our final best model predicts the high-z quintuply lensed system with a position accuracy of 0.8''. The magnifications of the five images are between 2.2 and 8.3, which leads to a delensed UV luminosity of L_1600 ~ 0.5L*_1600 at z=6. We also estimate the UV slope from the observed NIR colours, finding a steep beta=-2.89+-0.38. We use singular and composite stellar population SEDs to fit the photometry of the hiz candidate, and we conclude that it is a young (age <300 Myr) galaxy with mass of M ~ 10^8Msol, subsolar metallicity (Z<0.2Zsol) and low dust content (AV ~ 0.2-0.4).